Profiling of Parthenium (Parthenium hysterophorus L.) active compounds and allelopathic suppression of crops and weeds in bambara groundnut (Vigna subterranea L.) cultivation - Bashar, H M Khairul (2022)
Parthenium hysterophorus L. is a noxious herb with pharmaceutical properties and has allelopathic potentiality to retards the growth of many species. Hence, research was undertaken with the aim to identified phytotoxic compounds and determine the possibility of using aerial parts (leaf, stem and flower) of P. hysterophorus as a potential bioherbicide to control weed in Bambara groundnut field. The experiment was conducted in laboratory and glasshouse condition at University Putra Malaysia (UPM) using complete randomize design (CRD) and randomize complete block design (RCBD) accordingly. Germination of seeds and seedling growth of selected crops and weed species were tested with six concentrations of methanol, hexane, acetone, and water extracts (25, 50, 75, 100, and 150 g L-1) and distilled water as the control. The results showed that the phytotoxicity effects were significantly higher by leaf extract and methanol solvent compared to other treatments. The methanol extract of P. hysterophorus leaf sprayed as post-emergence applications on bambara groundnut (V. subterranean L.), maize (Z. mays), D. sanguinalis, E. indica, A. conyzoides, C. iria, E. hirta, C. difformis showed that the efficacy of the treatments were in the following trend; leaf>flower>stem and methanol>acetone>water>hexane. The liquid chromatography-mass spectrometry (LC-MS) analysis exposed the presence of 67 and 196 compounds in methanol, 60 and 191 in hexane, 75 and 77 in acetone, and 52 and 184 from water in both positive and negative polarity analysis. Seven phytotoxic derivatives were identified from the methanol solvents of leaf and flower but two and three compounds in acetone, hexane, and water extract respectively. On the other hand, high-performance liquid chromatography (HPLC) analysis confirmed methanol with leaf extracts contained a higher number and amount of chemical compounds than did those of the other solvent extracts. Caffeic acid, chlorogenic acid, and parthenin (highest allelopathic activity) were detected in the highest concentrations in the methanol leaf extract, but this compound was not found in the other extracts. P. hysterophorus methanol leaf extract administered to the test species at doses of 100 g L-1 showed a reduction in photosynthesis rate (22-83.37%), stomatal conductance (17-120.40%), transpiration (27.41%), chlorophyll content (13-143.87%), and carotenoid content (15-117.72%) at 6 hours after spray (HAS). The activities of antioxidant enzymes, malondialdehyde (MDA)(183-596%), Proline content (150-500%), superoxide dismutase (SOD)(76-95%), catalase (CAT)(98-208%), and peroxidase (POD)(94-212%) were also increased with the same concentrations at 72 HAS in different weeds. Present findings confirm that the methanol leaf extract of P. hysterophorus can disrupt the physiological and biochemical mechanism of target weeds. For field evaluation, treatment of P. hysterophorus leaf methanol extract (75, 100, and 150 g L-1) along with five chemical herbicides [chemical name % a.i. (Fusilade Forte 150 EC), chemical name % a.i. (Prowl ® 3.3 EC), chemical name % a.i. (Hextar Diuron 80wp), glyphosate 41% a.i. (Roundup®) and glufosinate-ammonium 13.5% a.i. (Basta®)] at 1 L ha-1, no herbicide treatment and weeding manually was done. It was observed that P. hysterophorus leaf methanol extract at the rate of 150 g L-1 and all chemical herbicides killed Bambara groundnut and most weeds. However, Bambara groundnut yielded the most when sprayed with P. hysterophorus leaf methanol extract at a rate of 100 g L-1 followed by manual (hand weeding). As a result, 100 g L-1 of P. hysterophorus leaf methanol extract could be sprayed to manage weeds without reducing Bambara groundnut yield. Based on these findings, P. hysterophorus leaf methanol extract can be utilized as a natural post-emergent herbicide in Bambara groundnut fields to suppress weeds, as well as for the development of novel herbicides based on phytotoxic chemicals generated by this plant.